Estimating crack widths in steel fibre-reinforced concrete. Issue 1 (20th February 2019) - Hover, Eyre; Psomas, Sotiris; Eddie, Colin
Abstract : The use of steel fibres as reinforcement for sprayed concrete tunnel linings offers significant potential savings in time and cost. These provide a degree of crack control and an increase in ductility to the otherwise brittle material, and while the properties of steel fibre-reinforced concrete (SFRC) are well understood, its ability to control cracks is not quantifiable or justifiable in the design of concrete sections. This paper describes the novel application of particle image velocimetry (PIV) to the study of cracking in plain concrete and SFRC four-point flexural beam tests. Strain hardening under bending was observed, as was the propagation of multiple cracks (multicracking) in SFRC beams, in contrast to the brittle failure of the plain concrete specimen. The stress–strain behaviour of the material was quantified by means of digital photographs of the test, and Young's modulus of the SFRC was found to be similar to that of plain concrete. Cracks on the side of the beam as small as 0·05 mm and up to 4 mm were measured with an error < 0·02 mm, making PIV a viable option for crack width analysis for the basis of SFRC design assisted by testing, supported by BS EN 1990.